2020
DOI: 10.3390/ma13173659
|View full text |Cite|
|
Sign up to set email alerts
|

VOC Emission Analysis of Bitumen Using Proton-Transfer Reaction Time-Of-Flight Mass Spectrometry

Abstract: Bitumen is one of the most important materials used in roads. During asphalt pavement construction, workers can be affected by emissions, such as volatile organic compounds (VOCs), when bitumen is heated. Therefore, it is crucial to correctly identify and measure VOCs. This paper presents a novel, promising method to determine VOC emissions. The proposed method offers a way to standardize routine measurements on a lab scale, enabling reliable comparison across bitumen types and their modifications or additives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 34 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…The MWD of the negative ion mode was located in the range of 10–600 Da. In previous research, headspace GC–MS was the most widely used asphalt fume analysis method, and the results of these works showed that the molecular weight of detected VOCs in asphalt fumes was below 400 Da. ,,,, In addition, none of the work has pointed out that the molecular weight of the compounds in asphalt fumes may be above 400 Da due to the limitation of the analysis method. However, the results obtained by the established method show that there are many peaks in the mass range of 400–800 Da, which indicates that the chemical composition of asphalt fumes is much more complex than the reported composition in previous literature.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MWD of the negative ion mode was located in the range of 10–600 Da. In previous research, headspace GC–MS was the most widely used asphalt fume analysis method, and the results of these works showed that the molecular weight of detected VOCs in asphalt fumes was below 400 Da. ,,,, In addition, none of the work has pointed out that the molecular weight of the compounds in asphalt fumes may be above 400 Da due to the limitation of the analysis method. However, the results obtained by the established method show that there are many peaks in the mass range of 400–800 Da, which indicates that the chemical composition of asphalt fumes is much more complex than the reported composition in previous literature.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As one of the most powerful analytical techniques, mass spectrometry has been widely used in the field of asphalt analysis. For example, thermal gravimetric analysis–mass spectrometry (TGA-MS), proton-transfer-reaction time-of-flight mass spectrometry (PTR-TOF-MS), and gas chromatography–mass spectrometry (GC–MS) have been used to assess the VOC emission in different asphalt materials. Among them, GC–MS has been used most frequently in asphalt fume analysis. , For example, GC–MS has been successfully used to analyze polycyclic aromatic hydrocarbons, , oxygenated VOCs, nitrogen VOCs, sulfur VOCs, and carboxylic acids in bitumen.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 1 , the relevant peer-reviewed journal articles were searched through Pubmed and Embase [ 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. The search expressions involved “rubber asphalt” and “emission” or “pollution” or “economic” or “energy consumption”.…”
Section: Sustainability Of Rubberized Asphaltmentioning
confidence: 99%
“…The emission of atmospheric pollutants by hot asphalt mixtures at deposition temperatures above 120 °C is well constrained at least regarding polycyclic aromatic hydrocarbons (PAHs), [22][23][24][25] and volatile organic compounds. [26][27][28] It is therefore striking that VOC emissions by asphalt mixtures at service temperatures, i.e. below 70 °C, had never been investigated before the year 2020.…”
Section: Introductionmentioning
confidence: 99%